Economic sustainability and community support by ex-migrants in rural communities in Lombok Tengah, Nusa Tenggara Barat - Sandiatmo Suyanto; Priyadi Budi Puspo; Falah Fajrul; Purwanti Tari; Putri Carolina Retmawati (E3S Web of Conferences)
This study explores the experiences of ex-migrant workers in Batukliang, Central Lombok, as they transition from overseas workforce to local entrepreneurship. With a focus on the challenges and motivations behind their entrepreneurial endeavours, the research delves into how these individuals leverage their skills, experiences, and limited resources to establish sustainable businesses in their home communities. Through purposive sampling, 24 ex-migrants participating in the Desmigrative program were interviewed, revealing a common thread of resilience and adaptability in the face of economic and regulatory constraints. The findings highlight the critical role of community support and the need for government intervention in encouraging these entrepreneurial activities. Despite the hurdles of minimal capital and limited land, these entrepreneurs contribute significantly to local economic development, particularly through small-scale enterprises such as brick molding, gardening, and poultry farming. The study underscores the importance of targeted policies and initiatives that enhance the capacity of ex-migrant entrepreneurs, ensuring their contributions to the community’s economic stability and sustainability.